Copper-catalyzed radical oxidative C(sp3)–H/C(sp3)–H cross-coupling between arylacetonitriles and benzylic compounds. Issue 48 (27th November 2020) - Xiao, Jing; Li, Fangshao; Zhong, Ting; Wu, Xiaofang; Guo, Fengzhe; Li, Qiang; Tang, Zi-Long
Abstract: For the first time, a novel copper-catalyzed direct C(sp 3 )–H/C(sp 3 )–H cross-coupling of arylacetonitriles with unactivated benzylic compounds was described, allowing various a-benzylated arylacetonitriles to be readily accessible under base-free conditions. Mechanistic investigations suggested that the reaction proceeds through radical process and the C(sp 3 )–H cleavage of arylacetonitriles probably is the rate-determining step. Graphical abstract: Image 1 Highlights: Readily available benzylic compounds were used as alkylation reagents. Good functional group compatibility. Various substituted nitriles could be synthesized via direct C(sp 3 )-H/C(sp 3 )-H oxidative radical cross-coupling reactions.